STRATEGI STIMULASI PERKEMBANGAN SOSIAL ANAK TAMAN KANAK-KANAK IZZUL ISLAM BENGKULU UTARA - Musroinah Musroinah; Serli Marlina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe strategies for stimulating children's social development at Izzul Islam Kindergarten in North Bengkulu. The focus of the study includes various teacher efforts to stimulate children's social skills, such as the ability to interact, cooperate, communicate, share, and adapt to the school environment and peers. This study also aims to determine the role of teachers and parents in supporting children's social development during the learning process. The study used a descriptive qualitative approach to obtain an in-depth picture of the social stimulation strategies implemented in the school environment. The research subjects consisted of teachers, children, and parents. Data collection techniques were carried out through observation, interviews, and documentation so that the data obtained were more complete and in accordance with real conditions in the field. The results of the study indicate that stimulation strategies implemented through group play activities, habituation, interpersonal communication, as well as providing motivation and guidance can help improve children's social development